As políticas educacionais em municípios que se orientam por referenciais freireanos: outro jeito de fazer escola - Denise Regina da Costa Aguiar (EccoS – Revista Científica)
This article aims to study the inf luence and contributions of the thought of Paulo Freire in the education systems, and more specifically, the proposed public educational policy, in the Municipal of São Paulo in the period 1989 to 1992 and the Municipal of Diadema, in the period 2005 to 2008, with the aim of illustrating the theory empirically Freire. The reseach has been developed through dissertations, analysis produced located in the CAPES database. In such study case it was used the following procedures: document verification, observation on the side of the participant and interviews performed. The results of such research here presented demonstrate that a public policy proposal, popular and democratic, a Freirean perspective is characterized by a school project bold, innovative, permanently under construction, another way of doing school, because it causes a break with activities and knowledge so ingrained in the organization of school in a banking concept of education focused on the selectivity and expulsion, particularly the lower classes access to knowledge, culture, the right to “be more” finally, the right to human ethic.